Teaching French as a Foreign Language (FFL) in the primary schools of the Nigerian Refugee Camp in Minawao, Mayo-Tsanaga Department/Far-North Region of Cameroon - Mahamat Alhadji; Mohamadou Bassirou Arabo (European Scientific Journal, ESJ, 2018)
The reflection on the particular conditions of teaching French as a Foreign Language (FFL) and the development of the professional skills of the teachers involved are relatively recent fields of research in Cameroon. The purpose of this study is to describe and understand the motives for teaching French as a foreign language to Nigerian refugee pupils at the primary schools of Minawao Camp in Mayo-Tsanaga Department/Far-North Region of Cameroon. The information gathered through semi-structured interviews with teachers (n=17) in relation to their initial and continuous training, teaching contexts and teaching practices, allowed us to note that the teachers who teach FFL in the primary schools of Minawao Camp are not sufficiently trained or equipped to teach FFL. The description of their teaching practices in the classroom reveals that they still confuse traditional teaching in an "ordinary classroom" with that of FFL. The incompatibility of terms of reference with the curriculumbeing implemented, the particular intercultural contexts of their students, makes the teaching process of FFL difficult and unstable. Teaching FFL imposes challenges on teachers. To this end, starting from the theory of the foundations of convergent didactics, it is necessary to proceed to the development of the cultural competence of the teachers in order to adapt them to the different types of interventions, audiences and teaching situations of the FFL.